Pengetahuan Lokal Pengelolaan Pohon Sialang Pada Suku Anak Dalam di Taman Nasional Buki 12 Provinsi Jambi - Jimmy Pardomuan Marpaung (The Ethnobiological Society of Indonesia, 2021)
Management of conservation areas cannot be separated from the existence of communities in and around conservation areas. Bukit Duabelas National Park (BDNP) is one of the conservation areas in Indonesia whose designation has a specific purpose, namely protecting the living space and livelihood of the Orang Rimba. One of the forest resources that has been used by Orang Rimba for a long time is forest honey produced by forest honey bees (Apis dorsata) which makes its nest in Sialang Trees. Orang Rimba has its own local knowledge in managing Sialang Trees and applies strict customary rules to protect the existence of Sialang Trees. This study aims to explain the mechanism of resource management based on the local knowledge of Orang Rimba in BDNP and practices that contribute to the conservation of these resources. Data was collected in the framework of a qualitative approach using participatory observation and in-depth interviews with key informants consisting of forest honey collectors and other stakeholders, and supported by literature studies. The results show that local knowledge supports the sustainability of forest honey harvests and shows a positive impact on biodiversity conservation in the National Park. However, local knowledge about the management of Sialang Trees in Orang Rimba has begun to decline due to a lack of interest in the younger generation in harvesting Sialang honey.